2010
DOI: 10.2174/156720110793566209
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Assam Bora Rice Starch as Plasma Volume Expander by Polymer Analysis

Abstract: Water soluble polysaccharides are currently finding increasing use as a basis material for plasma volume expander. In clinical setting it is desirable to have a precise knowledge of steric and chemical structure, since these affect the pharmacokinetics and pharmacology of plasma volume expander. Branch component of starch amylopectin is very similar in structure to glycogen, the reserve polysaccharide of animal and therefore is liable to be compatible with body tissue. The knowledge of weight average molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
2
13
1
Order By: Relevance
“…The higher the solution concentration is, the more viscous the solution becomes. The effect of starch concentration on solution's viscosity was also observed in the study by Bhattacharya et al, which showed that the viscosity of 6 % w/v starch was higher than 4 % w/v starch at different rotational speed for both treated and untreated starch [12].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The higher the solution concentration is, the more viscous the solution becomes. The effect of starch concentration on solution's viscosity was also observed in the study by Bhattacharya et al, which showed that the viscosity of 6 % w/v starch was higher than 4 % w/v starch at different rotational speed for both treated and untreated starch [12].…”
Section: Discussionsupporting
confidence: 67%
“…However, the pharmacological and clinical equivalence between potato starch-based versus waxy maize-based HES plasma expanders still needs to be investigated further. Even more recently, Ahmad and colleagues have presented an alternative source of starch, Assam Bora rice, for plasma expanders [11,12]. They have characterized Assam Bora rice starch in the view of the FTIR spectra, degree of branching, osmotic pressure and molecular weight-viscosity relationship to use as plasma expander.…”
Section: Introductionmentioning
confidence: 99%
“…All other chemicals used in the experiment were of analytical reagent grade and used without further purification. Starch was isolated by methods already established [11][12][13][14]. MTZ (> 99% purity) was obtained as a gift sample from Aarey Drugs & Pharmaceuticals Ltd, Mumbai, India.…”
Section: Methodsmentioning
confidence: 99%
“…Assam Bora rice, locally known as Bora Chaval, was first introduced in Assam, India from Thailand or Myanmar by Thai-Ahoms [9][10][11], which is now widely cultivated throughout the Assam. The starch obtained from Assam Bora rice is characterized by its high amylopectin content (i.e., > 95%) with branched waxy polymer which shows physical stability and resistance towards enzymatic action [10][11][12]. Assam Bora rice starch hydrates and swells in cold water forming viscous colloidal dispersion or sols, which are responsible for its bioadhesive nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation